Management Of Sindu Dwarawati Sanur Turtle Conservation As A Tourism Attraction In Sanur Tourism Area - Sonder, I Wayan (Politeknik Internasional Bali, 2024)
Sindu Dwarawati Turtle Conservation is one of the turtle conservation in the Sanur tourism area. This conservation was built as a concern of youth groups who were moved to save sea turtles, especially sea turtle eggs around Sanur Beach. This research was conducted to know the process of turtle conservation and its management as a tourist attraction at Sindu Dwarawati Turtle Conservation. Both primary and secondary data were collected by conducting interviews, observation, and documentation. Data sources in the research were determined using purposive sampling and accidental sampling techniques. The data were analyzed using the descriptive qualitative data analysis method. The results showed that Sindu Dwarawati Sanur conservation has succeeded in conserving and saving sea turtles as support for government programs. The management of this turtle conservation as a tourist attraction has fulfilled the elements of something to see, to do, to buy, and to buy and fulfills the A4 criteria (attraction, accessibility, amenity, and ancillary service). However, ancillary services need to be optimized with the establishment of a structured management institution in serving tourists.